“MARCHING AS TO WAR”: A LETTER FROM BRAZIL TO SOUTH AFRICA ABOUT LANDLESSNESS, AGRARIAN REFORM AND SOCIAL MOVEMENT STRUGGLES AGAINST NEOLIBERALISM - Karriem, Abdurazack (REVISTA NERA, 2012)
This paper utilises the Brazilian Landless Movement’s (MST) National March for Agrarian Reform as a lens through which to analyze the social movement challenge to the Lula government’s submission to neoliberalism and suggests lessons for movement activists in South Africa. In focusing on the national march, the paper highlights the importance of marches as a strategic weapon of struggle for the MST, and situates this in historical, philosophical and tactical context. This paper asserts that the MST’s stress on organisation building and political education, its ability to forge strong rural-urban alliances, and its strategic vision in moving beyond narrow corporatist struggles for land to take up broader national popular demands is fundamental to understanding the MST’s consistent mobilizing capacity and its status as a vibrant counterhegemonic actor in Brazilian national politics.